Patients with Dipper and Nondipper High-Normal Blood Pressure Were Associated with Left Ventricular Mass - Fan-kai Xiao; Ping Li; Zhan-ying Han; Li Jing; Shaohua Hua; Luo-sha Zhao (International Journal of Hypertension)
Purpose. High-normal blood pressure has been suggested to associate with target organ damage and higher left ventricular mass index (LVMI). Our aim is to find the association between people with high-normal blood pressure and their left ventricular mass index. Materials and Methods. Given a total of 181 people with office blood pressure, 24-hour ambulatory blood pressure monitoring, 35 of them are normotensive (BP < 130/85 mm Hg), and 146 people with high-normal blood pressure (BP 130–139/85–89 mm Hg), divide the high-normal blood pressure group into dipper and nondipper according to their ABPM in 24 hours. All of them were performed with echocardiography to calculate LVMI. Results. After adjusting for potential confounding factors, mean systolic blood pressure (BP) of the nondipper group is (119 + 9) mmHg in 24 h, which is significantly higher (p < 0.05) than in the dipper group (116 + 11) mmHg, indicating the mean systolic BP is associated with the dipper type (p < 0.05); furthermore, the higher nocturnal blood pressure is associated with the nondipper group significantly (p < 0.05), and LVMI ((121 ± 11) g/m2) of the nondipper group is also significantly higher than in the dipper group’s LVMI ((108 ± 12) g/m2) (p < 0.05). The multivariate linear regression analyses revealed significant and independent associations of LVMI with these factors: triglyceride (TG), total cholesterol (TC), low-density lipoprotein (LDL-C), and coefficient of variation of systolic and diastolic blood pressure in 24 hours. Conclusion. After multiple relevant clinical confounding factors were adjusted, patients with dipper and nondipper high-normal blood pressure had higher LVMI. Abnormalities in circadian blood pressure variability may be associated with the left ventricular hypertrophy.